Pengembangan dan Renovasi Sarana Prasarana Dalam Mendukung Pendidikan Bermutu Pada Anak Usia Dini - Hijriah, Hijriah; Hesti Rosita Dwi Putri; Andi Sahputra Depari (Madani: Jurnal Pengabdian Ilmiah, 2025)
Early childhood education at the kindergarten (TK) level is an important foundation for children's cognitive, social, and emotional development. The availability of adequate facilities and infrastructure and educational learning media greatly influence the quality of early childhood learning. This community service activity aims to support the improvement of the quality of education at TK Cempaka II through three main focuses, namely the provision of batik dip learning media as a means of artistic expression and cultural introduction; the provision of educational play tools such as puzzles and letter blocks for children's cognitive stimulation; and renovation of damaged school floorboards to create a safe and comfortable learning environment. The results of the activity showed an increase in children's participation and enthusiasm in learning activities, an increase in community understanding of the importance of educational facilities (from 47% to 53%), and the creation of a more appropriate learning space. This activity proves that simple but targeted interventions/focuses can have a real impact on supporting the quality education process for early childhood.